A Campylobacter integrative conjugative element with a CRISPR-Cas9 system targeting competing plasmids: a history of plasmid warfare?. Issue 5 (27th May 2022) - Vliet, Arnoud van; Charity, Oliver; Reuter, Mark
Abstract : Microbial genomes are highly adaptable, with mobile genetic elements such as integrative conjugative elements (ICE) mediating the dissemination of new genetic information throughout bacterial populations. This is countered by defence mechanism such as CRISPR-Cas systems, which limit invading mobile elements by targetting specific sequences on these elements. Here we have studied the distribution the pVir, pTet and PCC42 plasmids and a new 70-129 kb ICE (CampyICE1) in the foodborne microbial pathogens Campylobacter jejuni and Campylobacter coli. CampyICE1 contains a degenerated Type II-C CRISPR system consisting of a sole Cas9 protein, which is distinct from the previously described Cas9 proteins from C. jejuni andC. coli. CampyICE1 is highly conserved in structure and gene order, containing blocks of genes predicted to be involved in recombination, regulation and conjugation. CampyICE1 was detected in 134/5, 829 (2.3%) C. jejunigenomes and 92/1, 347 (6.8%) C. coligenomes. Similar ICE were detected in a number ofnon-jejuni/coli Campylobacter species, which lacked a CRISPR-Cas system. Finally, CampyICE1 contained 3 separate short CRISPR spacer arrays, and a total of 124 unique spacers were identified, of which 67 are predicted to target the Campylobacterplasmids pVir, pTet, and pCC42, and 12 predicted to target other Campylobacter plasmids (63.7%). The presence of a functional CampyICE1 Cas9 protein and matching anti-plasmid spacers was associated with the absence of these plasmids (186/214 genomes), implicating that the CampyICE1-encoded CRISPR-Cas has contributed the exclusion of competing plasmids. Hence the CampyICE1 CRISPR-Cas system may be a part of ongoing plasmid warfare in Campylobacter spp.